Tinjauan Yuridis Terhadap Layanan Jual Beli Account Netflix Premium Secara Ilegal - Ni Made Tessa Aprillia Dewi; I Nyoman Putu Budiartha; Ni Made Puspasutari Ujianti (Fakultas Hukum Universitas Warmadewa, 2025)
Netflix as a subscription streaming service for watching entertainment. Currently Netflix is not only used as a means of entertainment, but also used as a business object such as the sale of illegal Netflix accounts that harm copyright holders, and result in legal consequences for the perpetrators. The problem is 1. What are the legal consequences of the illegal sale of premium Netflix accounts that harm copyright holders? 2. What is the form of legal protection that can be given to the illegal sale and purchase of premium Netflix accounts? Finding out how big the impact of Netflix copyright infringement is and what laws are applied to prevent the unlawful sale of Netflix accounts are the two main objectives of this research. The method used in this research is normative legal research method. The legal consequences of selling illegal premium Netflix accounts are copyright infringement and violation of ITE law. Netflix as a creation that gets protection under copyright law while legal protection to account users from illegal sellers cannot be given and does not meet the objective requirements for the validity of an agreement, according to Article 1320 of the Civil Code paragraph (4), namely a halal cause.